GROWTH OF HETEROTROPHIC BACTERIA IN SEA WATER CONTAMINATED WITH RINSO DETERGENT - Effendi, Irwan; Tanjung, Cahyani Fitrah; Elizal, Elizal (Asian Journal of Aquatic Sciences, 2018)
This research was conducted in March-April 2017 at Marine Microbiology Laboratory, Faculty of Fisheries and Marine University of Riau. The purpose of this study is to determine the different concentration of detergent (0 ml/L, 1.5 ml/L, 3 ml/L, 4.5 ml/L, 6 ml/L) in different observation time (0, 5, 10, 15, 20) on the growth of heterotrophic bacteria in sea water. Completely randomized design was used in this experimental method. The results showed that bacterial growth of all treated samples decreased on the 5th day of incubation. However, the population began to increase on the 10th day of incubation. The count of maximum bacterial growth was 1.46 x 109 found in the 4.5 ml/L treated detergent, and the lowest growth was 3.73 x 107 in the 1.5 ml/L treated detergent. Statistical analysis (ANOVA) showed that the concentrations in different observation times on the growth of heterotrophic bacteria showed significant effect and the value was (P <0.005).